93.0k views
0 votes
In your notebook, set up the following subtraction in a vertical format and select the correct answer. Take -4 + 3a 2 from 7a - a 2.

2 Answers

4 votes
Are you sure this question is complete?

(7a - a²)
- (-4 + 3a²)
==========
(7a - a²)
+ (4 - 3a²)
==========
7a + 4 - 4a² = - 4a² + 7a + 4 ...//
User Cpres
by
6.1k points
6 votes
ANSWER


4 + 7a - 4{a}^(2)

Step-by-step explanation

We want to take,


- 4 + 3 {a}^(2)

from


7a - {a}^(2)

Mathematically we can write this statement as,


(7 a - {a}^(2) ) - ( - 4 + 3 {a}^(2) )

We use the distributive property to expand to obtain,


7 a - {a}^(2) + 4 - 3 {a}^(2)

We regroup to obtain,


4 + 7a - {a}^(2) - 3 {a}^(2)

This simplifies to


4 + 7a - 4{a}^(2)
User RedZ
by
6.2k points